Transcriptome Analysis of Wounding in the Model Grass Lolium temulentum - Dombrowski, James E. (Plants (Basel), 2020)
For forage and turf grasses, wounding is a predominant stress that often results in extensive loss of vegetative tissues followed by rapid regrowth. Currently, little is known concerning the perception, signaling, or molecular responses associated with wound stress in forage- and turf-related grasses. A transcriptome analysis of Lolium temulentum plants subjected to severe wounding revealed 9413 upregulated and 7704 downregulated, distinct, differentially expressed genes (DEGs). Categories related to signaling, transcription, and response to stimuli were enriched in the upregulated DEGs. Specifically, sequences annotated as enzymes involved in hormone biosynthesis/action and cell wall modifications, mitogen-activated protein kinases, WRKY transcription factors, proteinase inhibitors, and pathogen defense-related DEGs were identified. Surprisingly, DEGs related to heat shock and chaperones were more prevalent in the downregulated DEGs when compared with the upregulated DEGs. This wound transcriptome analysis is the first step in identifying the molecular components and pathways used by grasses in response to wounding. The information gained from the analysis will provide a valuable molecular resource that will be used to develop approaches that can improve the recovery, regrowth, and long-term fitness of forage and turf grasses before/after cutting or grazing.